Developing a Cost-Effective Air Quality Monitoring Solution Using IoT Technology: Addressing Long-Distance Transmission Challenge - Khonrang, Jarun; Winyangkul, Seksan; Duangnakhorn, Pairoj; Viratikul, Rungrat; Boonlom, Kamol (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2025)
This research explores the integration of Internet of Things (IoT) technology and LoRa repeaters to enhance air quality monitoring. IoT enables low-cost, real-time sensors for continuous air quality assessment, while repeaters address the limitations of traditional wireless communication over long distances. Our study demonstrates the effectiveness of a LoRa repeater system, with signal strengths between monitoring stations and repeaters ranging from -84 dBm to -92 dBm, achieving a practical operational range of 850 meters. The highest Packet Delivery Ratio (PDR) recorded was 65% using a Spreading Factor (SF) of 10, while SF 7 resulted in a PDR of 25%. Environmental factors and antenna gain were identified as critical for optimizing transmission power and communication reliability. This research underscores the potential of advanced IoT applications in extending internet connectivity and improving air quality management across various sectors, paving the way for smarter urban environments and public health initiatives.